2014
DOI: 10.1186/1944-3277-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of Coxiella burnetii strain Namibia

Abstract: We present the whole genome sequence and annotation of the Coxiella burnetii strain Namibia. This strain was isolated from an aborting goat in 1991 in Windhoek, Namibia. The plasmid type QpRS was confirmed in our work. Further genomic typing placed the strain into a unique genomic group. The genome sequence is 2,101,438 bp long and contains 1,979 protein-coding and 51 RNA genes, including one rRNA operon. To overcome the poor yield from cell culture systems, an additional DNA enrichment with whole genome ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 77 publications
0
6
0
1
Order By: Relevance
“…Interestingly, also lactate showed some minor 13 C-enrichment in the experiment with labeled serine (Figure 2A ). However, enzymes responsible for lactate biosynthesis from pyruvate seem not to be present in C. burnetii based on the genome sequence (Seshadri et al, 2003 ; Walter et al, 2014 ). Hypothetically, lactate could be produced from methylglyoxal due to detoxification reactions in this pathogen (Figure S2 , for more details, see also below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, also lactate showed some minor 13 C-enrichment in the experiment with labeled serine (Figure 2A ). However, enzymes responsible for lactate biosynthesis from pyruvate seem not to be present in C. burnetii based on the genome sequence (Seshadri et al, 2003 ; Walter et al, 2014 ). Hypothetically, lactate could be produced from methylglyoxal due to detoxification reactions in this pathogen (Figure S2 , for more details, see also below).…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, enzymes for the glyoxylate pathway have not been identified until now, indicating that Coxiella does not use fatty acids for energy generation in contrast to Mycobacterium tuberculosis (Schnappinger et al, 2003 ; Seshadri et al, 2003 ), although a putative transporter for long chain fatty acids (CBU1242) was assigned in the genome of C. burnetii (Kuley et al, 2015 ). Notably, the shikimate/chorismate pathway is also evident from the genome sequence although some late steps leading to the aromatic amino acids appear to be missing (Seshadri et al, 2003 ; Walter et al, 2014 ) (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sequenced reads were then de novo assembled using SPAdes [ 47 ] version 3.13. Finally, the contigs were polished using Pilon version 1.23 [ 48 ] in order to determine the number of IS 1111 elements, blastn of the BLAST + package [ 49 ] was used to align the conserved IS 1111 insertion sequence against the assembled contigs. All contig ends aligning to the IS 1111 insertion sequence were counted half; contigs fully covered by the insertion sequence were ignored.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2003, six new whole genomes of C. burnetii have become available in GenBank (142)(143)(144). Sixteen incomplete genomes can also be found (27,47,(145)(146)(147)(148)(149)(150). In 2009, Beare et al performed a comparative genomic analysis of four strains and found a total of 125 pseudogenes, of which 65 were highly conserved, and 8 IS families (142).…”
Section: Comparative Genomics and Pangenomic Analysismentioning
confidence: 99%